IMPORTANT AND PRIORITY DIRECTIONS FOR DEVELOPING THE EDUCATION SYSTEM IN OUR COUNTRY (International journal of artificial intelligence, 2026)
This article examines the essence and content of the new paradigm of the education system, its basic principles, as well as the features of personality-oriented learning. The content of the concept of the system-activity approach in its correlation with the innovative strategy of education was revealed.